2014
DOI: 10.1002/hed.23699
|View full text |Cite
|
Sign up to set email alerts
|

Association of differential β‐catenin expression with Oct‐4 and Nanog in oral squamous cell carcinoma and their correlation with clinicopathological factors and prognosis

Abstract: Background: The re-expression of pluripotent markers (Oct-4 and Nanog) and the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 39 publications
3
53
0
2
Order By: Relevance
“…Recent studies revealed that NANOG is highly detected in poorly differentiated carcinomas and late-stage tumors [8][9][10]. Moreover, a positive relationship between enhanced NANOG expression and lymph node metastasis of carcinoma was reported [21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies revealed that NANOG is highly detected in poorly differentiated carcinomas and late-stage tumors [8][9][10]. Moreover, a positive relationship between enhanced NANOG expression and lymph node metastasis of carcinoma was reported [21].…”
Section: Discussionmentioning
confidence: 99%
“…NANOG is an early transcription factor and pluripotent marker that maintains the self-renewal of embryonic and mesenchymal stem cells [8]. Recent studies revealed that NANOG is highly detected in poorly differentiated carcinomas and late-stage tumors [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations